COVID-19, frontline responders and mental health : a playbook for delivering resilient public health systems post-pandemic - Horney, Jennifer A. (Emerald Publishing Limited, 2023)
Since the declaration of the COVID-19 pandemic health care, public health, first responders, and other essential workers have been engaged in the most extensive emergency response in more than a century, whilst trust in science has been eroded and public health has been politicized. Against this context, the authors in this collection assess the potential mental health impacts, widening disparities, and needed interventions for future resilience of the public health workforce. What actions can be taken now to ensure more resilient systems post-pandemic? Focusing on the impacts of the pandemic on responder health across health care, public health, emergency management, and more, the chapters, written by experts in the field, provide an overview of the mental health impacts of disasters and emergencies on responders more broadly, and also highlight the inequitable impacts of the response among sectors of the workforce and populations who are socially or physically vulnerable. Closing with recommendations for changes that are needed to address gaps in capacity, COVID-19, Frontline Responders and Mental Health makes a crucial contribution to building the evidence base and disseminating best practices to ensure recommendations become standard practices in the future. Realizing the harsh potential realities such as a shortage of qualified workers and questions around funding and workforce development needed to ensure preparedness for the next public health emergency, this playbook for delivering resilient public health systems post-pandemic provides a timely oversight for future resilience.